Enhancing Cognitive Development through Solo Mathematical Play - Wynter, Alethea; Quasar, Elianore; Reyes, Kalliope; Blackwood, Thalia (Journal of Computer Engineering, 2022)
The aim of the paper is to introduce mathematical interactive games created with the support of the STEM4youth project (2016 – 2018). The games were designed for individuals and also for two competing players or two competing teams and they are distributed as PDF files. In the paper we focus on the games for one player - the Funny picture game and the Puzzle game. Finally, the experience with similar games (predecessors of the STEM4youth games) in Czech schools is also discussed.